Development and dissemination of a manual cassava chipper in Cameroon - Njukwe, E.; Duindam, J.; Hauser, S.; Maziya-Dixon, B.B.; Amadou Thierno, D.; Onadipe, O.; Mbairanodji, A.; Ngue-Bissa, T.; Kirscht, H.; Hanna, R. (International Association of Hydrological Sciences, 2012)
Cassava (Manihot esculenta Crantz) is the main starchy staple in many parts of Cameroon, with 80% of rural and urban households consuming cassava and cassava derived products on a daily basis. Cassava products are commercialized mostly to supply household consumer markets with a total estimated equivalent of 1.1 million ton fresh cassava consumed in 2002 mainly because processing rely highly on family labour. Because of the smallholder nature of farming systems and the low density of producers in more inaccessible areas, investment in immobile, motorized cassava processing equipment is often not economically justified by the production capacity in these areas. Hence, IITA developed manual cassava chipper that are, easily transported and don't rely on electricity or fuel and complex technology. This manual chipper was tested with farmers in several villages. It has a capacity to process up to 260 kg cassava per hour, which is enough for a several farming households to consume in two months. In January 2007, the IFAD-funded project, Programme National de Développement des Racines et Tubercules (PNDRT) embarked on a program to promote and disseminate an IITA manual cassava chipper within the framework of its efforts on value addition to enhance farmers' income in Cameroon. IITA in collaboration with PNDRT identified and trained 13 local fabricators and the chippers disseminated were fabricated locally. 100 machines are currently being used by over 100 groups of cassava growers in 25 villages totalling about 1500 farmers in the 10 regions of Cameroon. Several NGOs, CBOs and farmers' organizations in Cameroon have now engaged in the fabrication and dissemination of IITA manual cassava chipper. Users and beneficiaries of this processing technology are cassava growers and small agricultural machinery manufacturers. The design, specifications and the user's guide for the manual cassava chipper are available. We expect that this technology will improve the accessibility of mechanized processing and increase commercialization and subsequent income of cassava growers in Cameroon.